THE ROLE OF SUPREME AUDIT INSTITUTIONS IN ENSURING PUBLIC SECTOR ACCOUNTABILITY - Dito Aditia Darma Nst; Sundari Apriliani; Sabar Jaya Mendrofa (Cahaya Ilmu Bangsa, 2025)
The role of Supreme Audit Institutions (SAIs) is critical in ensuring accountability in the public sector. This article explores how SAIs contribute to enhancing transparency, effectiveness, and efficiency in public financial management, and how audit results function as tools for public oversight. Using literature review and comparative analysis of audit practices across countries, the study highlights the importance of independence, institutional capacity, and auditor integrity as key factors in SAI effectiveness. Findings indicate that strong SAIs can mitigate budget misuse, strengthen public trust, and promote public sector governance reforms. The article recommends strengthening legal frameworks and enhancing collaboration between SAIs and parliaments to optimize oversight functions. Keywords: Supreme Audit Institutions, public accountability, public sector, financial audit, governance